2015
DOI: 10.1371/journal.pone.0123080
|View full text |Cite
|
Sign up to set email alerts
|

The Carcinogenicity of Alendronate in Patients with Osteoporosis: Evidence from Cohort Studies

Abstract: ContextAlendronate may relate to the incidence of cancers, especially esophageal and colon cancer. But the results are inconsistent in different studies.ObjectiveTo quantify the association between the use of alendronate and the occurrence of different types of cancer.Data SourcesWe searched Embase, Pubmed, CENTRAL, SIGLE and clinicaltrials.gov, up to 2014 June.Study SelectionCohort studies reporting association between alendronate or bisphosphonate therapy including alendronate in patients with osteoporosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
(59 reference statements)
2
11
0
Order By: Relevance
“…However, the randomized control trials were not initially designed to study breast cancer outcome and they might be at high risk of selective reporting bias. Overall, systemic reviews and metaanalyses agreed upon a signi cantly decreased risk of primary breast cancer in bisphosphonates users [24][25][26]. This is in accordance with our ndings.…”
Section: Comparison Of Our Results With Other Studiessupporting
confidence: 91%
See 1 more Smart Citation
“…However, the randomized control trials were not initially designed to study breast cancer outcome and they might be at high risk of selective reporting bias. Overall, systemic reviews and metaanalyses agreed upon a signi cantly decreased risk of primary breast cancer in bisphosphonates users [24][25][26]. This is in accordance with our ndings.…”
Section: Comparison Of Our Results With Other Studiessupporting
confidence: 91%
“…The entangled and far-reached regulatory network is summarized in Figure 1 Epidemiological studies have shown that bisphosphonates have variable non-adverse, e.g. protective or no related risk towards female breast cancer [15][16][17][18][19][20][21][22][23][24], although some reports showed that alendronate may be associated with higher risks in lung and liver cancers [25,26]. A recent study suggests a potential protective effect of denosumab ever use on breast cancer risk in a cohort of older women previously treated with bisphosphonates [27].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, systemic reviews and meta-analyses agreed upon a significantly decreased risk of primary breast cancer in bisphosphonates users [24][25][26]. This is in accordance with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…There is a long‐standing debate about the relationship between bisphosphonate use and cancer risk. Several observational studies have discussed the use of bispho1sphonate as potential chemoprevention against various cancers—colorectal cancer, breast cancer, gastrointestinal cancer, and esophageal cancer, but the results were inconsistent. It still remains unclear whether bisphosphonate exert an anticancer effect or not.…”
Section: Discussionmentioning
confidence: 99%